2016
DOI: 10.1021/acs.est.6b00961
|View full text |Cite
|
Sign up to set email alerts
|

Organic Nitrate Contribution to New Particle Formation and Growth in Secondary Organic Aerosols from α-Pinene Ozonolysis

Abstract: The chemical kinetics of organic nitrate production during new particle formation and growth of secondary organic aerosols (SOA) were investigated using the short-lived radioactive tracer (13)N in flow-reactor studies of α-pinene oxidation with ozone. Direct and quantitative measurements of the nitrogen content indicate that organic nitrates accounted for ∼40% of SOA mass during initial particle formation, decreasing to ∼15% upon particle growth to the accumulation-mode size range (>100 nm). Experiments with O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 69 publications
8
54
0
Order By: Relevance
“…In this study, we found that PM 2.5 concentrations in Beijing were lower in summer than in winter, while O 3 concentrations were higher in summer than in winter. Higher PM 2.5 concentrations were observed in winter, which is attributed to a large number of anthropogenic emissions from biomass burning and combustion of fossil fuels and unfavorable weather conditions (e.g., low temperature, weak solar radiation, and low boundary layer height) for the dilution and diffusion of PM 2.5 [8,34,58]. Meteorological factors and O 3 precursors are linked to O 3 formation [59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that PM 2.5 concentrations in Beijing were lower in summer than in winter, while O 3 concentrations were higher in summer than in winter. Higher PM 2.5 concentrations were observed in winter, which is attributed to a large number of anthropogenic emissions from biomass burning and combustion of fossil fuels and unfavorable weather conditions (e.g., low temperature, weak solar radiation, and low boundary layer height) for the dilution and diffusion of PM 2.5 [8,34,58]. Meteorological factors and O 3 precursors are linked to O 3 formation [59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…The absence of NH 4 and the ratio of the peaks associated with ammonium nitrate make it unlikely that the NO 3 signal represents ammonium nitrate (Fry et al, 2009;Bruns et al, 2010). It may be, at least to a large part, indicative of organonitrates, which have been shown to account for 15-40 % of SOA mass in laboratory experiments (Berkemeier et al, 2016) and whose formation is enhanced at low temperatures .…”
Section: Chemical Compositionmentioning
confidence: 99%
“…112 Additionally, the interaction of ozone with organic aerosols, especially those containing unsaturated bonds, has been extensively studied. 55,113117 …”
Section: Bioaerosol Reactivity – Oxidant Chemistry and Other Reactionmentioning
confidence: 99%